Do Poverty and Human Development Index Influence Happiness? Evidence from Indonesia through Islamic Studies Approach - Dini Maulana Lestari; Aziz Muslim; Reni Furwanti; Iin Solikhin (el-Jizya: Jurnal Ekonomi Islam, 2022)
This research aims to examine the relationship between poverty and human development index to happiness rate in Indonesia through Islamic studies approach. This is because poverty Indonesia till become a prominent economic issue but, it has a high rate of happiness compared to another developed country in ASIA at the same time. Besides, to reach such happiness, it also needs a great human development as an indicator to create welfare of such countries. This is a quantitative research with multiple regressions, using macro-economic data since 2014 & 2017 from 33 provinces of Indonesia as a sample. The result revealed that poverty and human development index have a positive significant effect on happiness. Then, this empirical finding is in line with the concept of maqāṣid al-syariah, specifically hifdz al- dīn and hifdz al-‘aql.